1992
DOI: 10.1007/bf00229009
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic hyperactivity after partial fornix section: role in cholinergic dependent memory performance

Abstract: Rats with unilateral or bilateral partial section of the fornix were impaired on an eight arm radial maze task. Neurochemical analysis of hippocampal tissue four weeks after the lesions revealed a 50% reduction of choline acetyltransferase (ChAT) activity. The cholinergic marker was correlated negatively with the number of errors in the maze; the lower the ChAT activity, the higher the error score. The fornix lesion also induced a 50% reduction in norepinephrine (NE), but no change in the noradrenergic metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…There is some material specificity in the expected direction, with left fornix damage tending to lead to verbal memory deficits and right fornix damage being more associated with visual memory deficits (Gaffan et al, 1991;McMackin, Cockburn, Anslow, & Gaffan, 1995). However, it is worth noting that the extent of damage is more predictive of deficits than the lesion location on both verbal and visual tasks (Korematsu, Hori, Morioka, & Kuratsu, 2010;Sara, Dyon-Laurent, Guibert, & Leviel, 2004 for an animal model).…”
Section: Lesions Of the Human Fornixmentioning
confidence: 99%
“…There is some material specificity in the expected direction, with left fornix damage tending to lead to verbal memory deficits and right fornix damage being more associated with visual memory deficits (Gaffan et al, 1991;McMackin, Cockburn, Anslow, & Gaffan, 1995). However, it is worth noting that the extent of damage is more predictive of deficits than the lesion location on both verbal and visual tasks (Korematsu, Hori, Morioka, & Kuratsu, 2010;Sara, Dyon-Laurent, Guibert, & Leviel, 2004 for an animal model).…”
Section: Lesions Of the Human Fornixmentioning
confidence: 99%
“…These researchers postulated that the negative correlation between ChAT activity and NE turnover suggested that hyperactivity in the remaining noradrenergic neurons inhibited proper functioning of the remaining cholinergic neurons. 236 This is a remarkably similar pathology to that seen in AD and warrants further exploration. It is important to note that the suspected mechanism of noradrenergic inhibition on the cholinergic system operated through the α 2 receptors located on cholinergic terminals.…”
Section: Adrenergic and Cholinergic Relationshipmentioning
confidence: 67%
“…It was found that choline acetyltransferase (ChAT) activity was reduced by 50%, correlating negatively with the number of errors the rats made in a maze task, while hippocampal NE also decreased by 50%. 236 Interestingly, there was no decrease, and in fact a slight increase in the noradrenergic metabolite methylhydroxyphenylglycol (MHPG), suggesting a net increase in NE turnover despite the decrease in noradrenergic cells. These researchers postulated that the negative correlation between ChAT activity and NE turnover suggested that hyperactivity in the remaining noradrenergic neurons inhibited proper functioning of the remaining cholinergic neurons.…”
Section: Adrenergic and Cholinergic Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this antagonism, depleting the ACh level in the model has somewhat similar effects to enhancing NE; and depleting NE is similar to enhancing ACh. Intriguingly, Sara and colleagues have found similarly antagonistic interactions between ACh and NE in a series of learning and memory studies (Sara, 1989;Ammassari-Teule, Maho, & Sara, 1991;Sara, Dyon-Laurent, Guibert, & Leviel, 1992;Dyon-Laurent, Romand, Biegon, & Sara, 1993;Dyon-Laurent, Hervé, & Sara, 1994). They demonstrated that learning and memory deficits caused by cholinergic lesions can be alleviated by the administration of clonidine (Sara, 1989;Ammassari-Teule et al, 1991;Sara et al, 1992;Dyon-Laurent et al, 1993), a noradrenergic α-2 agonist that decreases the level of NE (Coull, Frith, Dolan, Frackowiak, & Grasby, 1997).…”
Section: Attention For Learningmentioning
confidence: 97%